Development of innovative refractory tile based on phase change material to improve efficiency of waste energy plant - Tan, Qi Chen (2017)
This study reports that the feasibility of a PCM containment or a refractory brick that would increase the efficiency of the current waste to heat recovery system in the industry. Firstly, various materials were discussed to identify which materials are suitable to be used as phase change material and the containment of the phase change material. Aluminum was chosen as PCM due to favorable properties such as high thermal conductivity, high melting point for high temperature thermal energy storage environment, high latent heat of fusion as well as low cost. Alumina was chosen as the containment material due as it is corrosion resistant and have favorable properties such as high modulus of rupture and thermal conductivity. Thermo-mechanical simulation analysis such as Ansys APDL and AutoDesk Mechanical Simulation were done on various designs of the refractory brick and an innovative design of the brick was concluded to be a basis for further development. Dynamic Mechanical Analysis as well as 3 Point Bending Test were conducted to further understand the material properties of alumina and aluminum.